Environmental social science and urban environment management: A review of pathways link- ing policies and planning to citizens living by the river - Mousazadeh, Hossein (Quaestiones Geographicae, 2022)
Urban environment management (UEM) and environmental social science (ESS) are two interconnected approaches that show significant potential for creating more sustainable and liveable cities. Their research has, however, been mainly disjointed, which may be because planning and policy have placed more emphasis on UEM than ESS at the same time. This research examined ESS in terms of the quality of life (QOL) criteria and sense of place (SOP) of citizens living by the river with the UEM intervention in the form of policies and programmes. The effects of fieldwork in the form of specialised and spatial interviews are presented in this research, which is usually ignored in the literature review of this type of analysis. The study aims to fill the current gap in this field in three European capitals by providing a reflective methodological account of fieldwork and the ‘elite interviewing’ approach. This paper produces a distinct form of the localisation of the research and sampling techniques and is as new, interactive and developing as possible. The results of the present study are underpinned by the conceptual model of research, which supports the main aim of this analysis and tries to examine the components of research in a new perspective. The findings high- lighted that maintaining and strengthening ESS for citizens living next to rivers require innovative UEM, which uses urban creativity in the field of goals, urban settlements, strategies and management solutions to provide the base for increasing the liveability of the city and improving the quality of urban life.